Sistem Pendukung Keputusan Pemilihan Platform Digital untuk Meningkatkan Brand Awareness Produk UMKM Menggunakan Metode TOPSIS - Enok Tuti Alawiah; Sunarti Sunarti; Omar Pahlevi (Fakultas Ilmu Komputer, Universitas Dian Nuswantoro, 2026)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize digital platforms as a marketing tool to increase product brand awareness. However, the large number of digital platform options makes it difficult for MSMEs to determine the most effective platform. This study aims to develop a Decision Support System (DSS) in selecting digital platforms to increase MSME product brand awareness using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This study uses a quantitative approach by collecting data through questionnaires from MSMEs in Bogor Regency. The criteria used include customer reach, engagement level, promotion costs, ease of use, ease of features, and payment methods. The TOPSIS calculation results show that TikTok obtained the highest preference value of 0.657, followed by Shopee Marketplace at 0.574, Instagram at 0.473, Tokopedia at 0.441, and Facebook Pro at 0.392. These findings indicate that TikTok is the most recommended digital platform in increasing MSME brand awareness because it has a wide reach and high level of interaction. Thus, the implementation of TOPSIS-based DSS has been proven to be able to provide objective and systematic digital platform recommendations, thereby helping MSMEs formulate more effective and data-driven digital marketing strategies.